The Value of Herbarium Collections to the Discovery of Novel Treatments for Alzheimer’s Disease, a Case Made With the Genus Eriodictyon - Maher, Pamela; Fischer, Wolfgang; Liang, Zhibin; Soriano-Castell, David; Pinto, Antonio F. M.; Rebman, Jon; Currais, Antonio (Frontiers in Pharmacology, 2020)
Plants, in particular those with a history in traditional medicine, hold enormous potential as sources of new therapies for dementias such as Alzheimer's disease (AD). The largest collections of plants can be found in herbaria all over the world, but the value of these collections to AD drug discovery has been significantly neglected. As a proof of principle, we investigated the neuroprotective activity of herbarium specimens of Eriodictyon (yerba santa), a genus with a long history of usage by the indigenous tribes in California to treat respiratory and age-related complications. Dichloromethane extracts were prepared from leaves of 14 Eriodictyon taxa preserved in the SD Herbarium located at the San Diego Natural History Museum. The extracts were tested for neuroprotection in nerve cells against oxytosis and ferroptosis and for anti-inflammatory activity in brain microglial cells exposed to bacterial lipopolysaccharide. In parallel, the levels of the flavanones sterubin, eriodictyol and homoeriodictyol were measured by mass spectrometry. Several Eriodictyon species presented strong neuroprotective and anti-inflammatory activities. The protective properties of the extracts correlated with the amount of sterubin, but not with eriodictyol or homoeriodictyol, indicating that sterubin is the major active compound in these species. The occurrence of eriodictyol and homoeriodictyol may be predictive of the phylogenetic relationship between members in the genus Eriodictyon. The data offer insight into the traditional use of yerba santa across indigenous tribes in California, while demonstrating the value of herbarium collections for the discovery of novel therapeutic compounds for the treatment of neurodegenerative diseases.